2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26976
|View full text |Cite
|
Sign up to set email alerts
|

From Problem Solvers to Problem Seekers: The Necessary Role of Tension in Engineering Education

Abstract: In this paper it is proposed that the current focus on problems in engineering education and technological literacy may be more constructively reframed by focusing on tensions. Priyan Dias claims engineering has an identity crisis that arises from tensions inherent in: 1) the influence of the profession on society, 2) the role engineers play, and 3) what constitutes valid knowledge in engineering. These are ethical, ontological, and epistemological tensions respectively, which Dias frames as a tension between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Similarly, sociotechnical dualism and the de-prioritization of the Social in engineering were often cited in our data (e.g., Celik et al, 2020;Li et al, 2019;Rottmann & Reeve, 2020;Swartz et al, 2019). Cheville and Heywood (2016) suggested that relative prioritizations and goals of engineering and engineering education are ongoing and omnipresent tensions. Reframed as tensions, diversity and ethics then are not problems for engineering educators to solve; rather, they are topics with "fundamental tensions" that engineering educators should discuss and debate.…”
Section: Sub-theme 22: Disciplinary Culturessupporting
confidence: 57%
See 3 more Smart Citations
“…Similarly, sociotechnical dualism and the de-prioritization of the Social in engineering were often cited in our data (e.g., Celik et al, 2020;Li et al, 2019;Rottmann & Reeve, 2020;Swartz et al, 2019). Cheville and Heywood (2016) suggested that relative prioritizations and goals of engineering and engineering education are ongoing and omnipresent tensions. Reframed as tensions, diversity and ethics then are not problems for engineering educators to solve; rather, they are topics with "fundamental tensions" that engineering educators should discuss and debate.…”
Section: Sub-theme 22: Disciplinary Culturessupporting
confidence: 57%
“…Each sub‐theme was present in at least 10 articles (i.e., more than 25%). Authors offered other lenses to connect ethics and DEI in engineering, including macro‐ethics and micro‐ethics (Bielefeldt et al, 2018), inclusive innovation (Li et al, 2019), rights of persons (Tooley & Umphress, 2009), and other philosophical frameworks (Cheville & Heywood, 2016). Hence, the sub‐themes we present here are not exhaustive of all Lenses for connecting ethics/DEI presented in the literature that we analyzed, nor are lenses mutually exclusive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this complex nature of engineering, many have argued that through design, approaches to engineering problems should be understood as frames rather than solutions [11], [52]. Often, outcomes in engineering are attempting to reach a decided value based on context and perceived need rather than a universal solution.…”
Section: Engineering Research Paradigmsmentioning
confidence: 99%